Advocating BPJS Salary Justice: A Local Income-Based Perspective - Rumintjap, Friedrich Max; Palupi, Merry Fridha Tri (PT FORMOSA CENDEKIA GLOBAL, 2023)
BPJS Health has successfully covered millions of participants across Indonesia, bringing the hope of affordable and quality health care for the people. However, this success is not apart from the serious debate on issues of justice in the BPJS allowance system, which is the main highlight and the main challenge facing BPJS health. Justice in the BPJS has become an increasingly relevant issue amidst the high economic and social diversity in Indonesia. The country covers a wide range of communities, ranging from high-income urban residents to rural residents who may only generate minimal incomes. There are significant differences in economic capacity between the inhabitants of big cities and small cities, as well as between different provinces.